Factors Affecting Consumers' Purchase Intention through Live Streaming: The Case of Footwear Products in Vietnam - Dang Thi Thu , Trang; Le Thi Hoang , Diem (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study aims to explore the factors that influence consumers’ live-streaming purchase intention for footwear products at e-commerce platforms. After analysing data collected from 341 consumers aged 16 to 40 years old in Vietnam using PLS-SEM, the result shows that trustworthiness, parasocial relationships, social presence, entertainment, and informativeness have direct and positive impacts on consumers purchase intention to buy footwear through live-streaming. Meanwhile, trustworthiness, expertise, and attractiveness indirectly and positively impact consumers' intention to purchase footwear through parasocial relationships. Based on these results, some managerial and practical implications were proposed to help retailers promote the consumers’ purchase intention to buy footwear via live-streaming in the most effective way.
Keywords: Informativeness; Live-streaming; Parasocial relationships; Purchase intention; Social presence; Trustworthiness